The philosophical foundations of extraterritorial punishment - Chehtman, Alejandro (Oxford : Oxford University Press, 2010)
The principle of extraterritorial punishment, which enables national courts to exert jurisdiction over crimes committed abroad by nationals of other states, has become more accepted. This book provides an account and critique of this form of jurisdiction, exploring its links to globalization, terrorism and transnational crime.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal jurisdiction; Exterritoriality; Punishment; Punishment -- Philosophy